2012
DOI: 10.1007/s00246-012-0612-1
|View full text |Cite
|
Sign up to set email alerts
|

Ratio of Early Diastolic Tricuspid Inflow to Tricuspid Lateral Annulus Velocity Reflects Pulmonary Regurgitation Severity but Not Right Ventricular Diastolic Function in Children With Repaired Tetralogy of Fallot

Abstract: The current study assessed relationships between the ratio of early diastolic tricuspid inflow to tricuspid lateral annular velocity (tricuspid E/e') and right ventricular (RV) function in children after tetralogy of Fallot (TOF) repair. The RV function of 25 asymptomatic children with surgically repaired TOF (age 3.3 ± 2.0 years) was assessed by echocardiography and cardiac catheterization. Right ventricular end-diastolic pressure and volume (RVEDP and RVEDV), systolic pressure, and ejection fraction, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 23 publications
6
15
0
Order By: Relevance
“…However, our findings are similar to prior studies in patients with TOF, which have shown no association between E/e′ and RV filling pressures in both pediatric and adult populations . One explanation for this finding could be the use of adult guidelines, which may not be reflective of the age‐related variation in echocardiographic parameters.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…However, our findings are similar to prior studies in patients with TOF, which have shown no association between E/e′ and RV filling pressures in both pediatric and adult populations . One explanation for this finding could be the use of adult guidelines, which may not be reflective of the age‐related variation in echocardiographic parameters.…”
Section: Discussionsupporting
confidence: 88%
“…Prior studies in adults without congenital heart disease have shown modest to excellent correlation between right atrial pressures and tricuspid valve E/A and E/e′ in varied populations,[5][6][7]18 as well as associations between echocardiographic parameters and improved clinical status in response to therapy in patients with pulmonary hypertension and subclinical hypothyroidism 19,20. These findings would suggest that tricuspid inflow and tissue Doppler parameters are valid measures of RV filling pressures.However, our findings are similar to prior studies in patients with TOF, which have shown no association between E/e′ and RV filling pressures in both pediatric and adult populations 12,21. One explanation for this finding could be the use of adult guidelines, which may not be reflective of the age-related variation in echocardiographic parameters.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…Previous reports that have described diastolic dysfunction in patients with repaired TOF have reported lower tricuspid annular e′ values and higher E/e′ ratios compared with our population. 8,28 This difference may be due to differences in operative technique or regional comorbidities. Conversely, the incidence of restrictive right ventricular physiology was similar in our cohort compared with other studies.…”
Section: Discussionmentioning
confidence: 99%
“…E’/A’ and E/E’ ratios are measured for an assessment of right ventricular diastolic function. An early diastolic tricuspid inflow assessed using standard echocardiography technique is designated as E. Studies in adults have shown that increased E/E’ ratio is closely associated with right ventricular filling pressure ( 12 ) , however, this relationship has not been confirmed in pediatric patients after teratology of Fallot repair ( 13 ) .…”
mentioning
confidence: 99%